Anionic currents in hypoxia-mediated cardiac toxicity: A computer study - Zoltani, C. K.; Baskin, S. I. (Cellular and Molecular Biology, 2007)
Hypoxia-caused modulation of cardiac electrophysiology was modeled by computer simulation. Emphasis was on the effect of activation of anionic channels on the electrical state of the tissue. The model includes implicitly the effect of the presence of reactive oxygen species (ROS) and nitrogen oxide (NO) on myocyte membrane voltage by their contribution to the activation of chloride currents. Three anionic currents were added to the modified Luo-Rudy ionic model of the ventricular action potential used in these calculations. The effect of the activation of the usually dormant currents due to hypoxia results in the modulation of the morphology of the action potential and the ECG. Transition of the ECG to ventricular fibrillation is shown. An important finding reported here is that control of the swelling and protein kinase C (PKC)-activated chloride currents can limit the electrical chaos of pharmacologically-caused hypoxic cardiac toxicity.